Different Associated Factors of Subjective Cognitive Complaints in Patients With Early- and Late-Onset Parkinson's Disease - Xiao, Yi; Ou, Ruwei; Yang, Tianmi; Liu, Kuncheng; Wei, Qianqian; Hou, Yanbing; Zhang, Lingyu; Lin, Junyu; Shang, Huifang (Frontiers in Neurology, 2021)
Background: Subjective cognitive complaints (SCCs), which are associated with a higher risk of cognitive decline, are widespread in the patients with Parkinson's disease (PD). The previous studies have reported inconsistent factors related to SCCs in the patients with late-onset PD (LOPD), and there is limited information on SCCs in the patients with early-onset PD (EOPD). Objective: We aimed to investigate the factors associated with SCCs in the drug-naïve patients with EOPD and LOPD without cognitive impairment. Methods: This cross-sectional study included 332 drug-naïve patients with PD, among whom 134 were EOPD and 198 were LOPD. Motor and non-motor symptoms, such as global objective cognitive status, depression, anxiety, apathy, fatigue, sleep, rapid eye movement sleep behavior disorder, orthostatic hypotension, and excessive daytime sleepiness, were assessed. Results: Twenty-five (18.66%) patients with EOPD and 49 (24.74%) patients with LOPD reported SCCs. A multivariate binary logistic regression analysis revealed that older age at onset [odds ratio (OR) = 1.24, P = 0.002], higher apathy score (OR = 1.13, P = 0.003), and lower scores in the visuospatial/executive abilities (OR = 0.25, P < 0.001) and memory (OR = 0.50, P = 0.024) domains of the Montreal Cognitive Assessment were associated with a higher risk of SCCs in the EOPD group. Higher apathy (OR = 1.06, P = 0.011) and anxiety (OR = 1.14, P < 0.001) scores were associated with SCCs in the LOPD group. Conclusion: Subjective cognitive complaints are only associated with mood disorders in patients with LOPD. In addition, SCCs may reflect subthreshold cognitive impairment in the patients with EOPD.